2008
DOI: 10.1158/1055-9965.epi-08-0312
|View full text |Cite
|
Sign up to set email alerts
|

Genomic DNA Methylation among Women in a Multiethnic New York City Birth Cohort

Abstract: One plausible mechanism for the environment to alter cancer susceptibility is through DNA methylation. Alterations in DNA methylation can lead to genomic instability and altered gene transcription. Genomic DNA methylation levels have been inversely associated with age suggesting that factors throughout life may be associated with declines in DNA methylation. Using information from a multi-ethnic New York City birth cohort (born between 1959 and 1963), we examined whether genomic DNA methylation, measured in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
147
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 23 publications
13
147
3
2
Order By: Relevance
“…Instead global DNA hypermethylation was observed in children whose mothers smoked during pregnancy. 39 These and our findings are in line with the global hypermethylation found in the sperm of mice exposed for 3 weeks to particulate air pollution of urban/ industrial source, in which PAH exposure was confirmed by the presence of elevated PAH-DNA adduct levels in the mice lungs. 15 Moreover, following in vitro chronic exposure to B[a]P, global DNA hypermethylation was associated to DNMT1 overexpression in mouse embryonic fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…Instead global DNA hypermethylation was observed in children whose mothers smoked during pregnancy. 39 These and our findings are in line with the global hypermethylation found in the sperm of mice exposed for 3 weeks to particulate air pollution of urban/ industrial source, in which PAH exposure was confirmed by the presence of elevated PAH-DNA adduct levels in the mice lungs. 15 Moreover, following in vitro chronic exposure to B[a]P, global DNA hypermethylation was associated to DNMT1 overexpression in mouse embryonic fibroblasts.…”
Section: Discussionsupporting
confidence: 91%
“…There is a growing body of evidence suggesting that human DNA methylation is responsive to environmental exposures during both intrauterine development and after birth in humans (68)(69)(70)(71)(72)(73).…”
Section: First Studies Of Deep Archeology Of Biological Embedding In mentioning
confidence: 99%
“…12 To date, however, few studies have examined differential methylation by race in histologically normal tissues. [13][14][15] Among them, analyses have been limited to global methylation and to blood specimens. 13,14 In one study to examine genomewide methylation differences by race, Adkins et al reported 3,623 loci in DNA significant differentially methylated between AAs and EAs at birth using umbilical cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Among them, analyses have been limited to global methylation and to blood specimens. 13,14 In one study to examine genomewide methylation differences by race, Adkins et al reported 3,623 loci in DNA significant differentially methylated between AAs and EAs at birth using umbilical cord blood. 15 However, to our knowledge, no study has comprehensively examined differences in methylation by race of genome-wide DNA methylation in normal breast tissues.…”
Section: Introductionmentioning
confidence: 99%